Effect of planter speed and seed firmers on corn stand establishment - Staggenborg, Scott A.; Taylor, R. K.; Maddux, Larry D. (My University, 2008)
Proper planter adjustment and operation play an important role in uniform stand establishment for corn. A two−year study was conducted to assess the impact of planter speed and a seed−firming device on corn stand establishment and grain yield. A planter equipped with a vacuum metering system and commercial seed firming devices was used in this study. Corn was seeded in a randomized complete block experiment at three speeds at two locations in Kansas (USA). Plant stand was counted at regular intervals after the first plant emerged to determine emergence rate. Plant spacing within each treatment was measured after complete emergence. Mean plant spacing, standard deviation in spacing, and four spacing indices (miss, multiple, quality of feed, and precision) were calculated to evaluate the plant spacing data. The miss and multiple indices indicate the number of skips and doubles. Planter performance as measured by these indices and standard deviation in plant spacing decreased as planter speed increased. The seed firmer reduced plant spacing standard deviations at a rate equivalent to the standard deviation increase observed when planter speed increased approximately 1.6 km/h (1 mph). Corn yield was reduced as planter speed increased at one location, but not the others. This response was the result of lower plant densities at the higher planter speeds, suggesting that one of the goals of the planting process should be to establish adequate plant densities. The seed firmer had no impact on corn yield.
Citation: Applied Engineering in Agriculture. Vol. 20(5): 573-580 . (doi: 10.13031/2013.17457) @2004
Keywords: Corn; Speed; Yield; Indices